Impacts of visitor trampling on the taxonomic and functional community structure of calcareous grassland. Issue 3 (24th February 2015) - Conradi, Timo; Strobl, Katharina; Wurfer, Anna‐Lena; Kollmann, Johannes; Paruelo, José
Abstract Question Does long‐term visitor trampling close to hiking trails affect the taxonomic and functional composition and diversity of a calcareous grassland, thus reducing its nature conservation value? Location Ancient calcareous grassland (nature reserve Garchinger Heide) in the Munich Gravel Plain, south Germany. Methods We sampled plant species composition at four distance classes representing different trampling intensities along replicated transects running perpendicular to 20‐yr‐old hiking trails in the nature reserve. We used a combination of distance‐based multivariate methods and a series of univariate tests to study the effects of trampling on a number of conservation‐relevant aspects of taxonomic and functional plant community composition and diversity. Results The different trampling intensities led to a significant variation in plant species composition that was driven by trait‐mediated responses, mainly of traits related to dispersal and regeneration, but these patterns only occurred close to the trails (<1.5 m). Except directly on the trails, species richness, the number of habitat specialists and threatened species, as well as Functional Richness were not or marginally affected by trampling. Multivariate dispersion within levels of trampling intensities and evenness, the latter measured for either species or traits, remained constant across the gradient of trampling intensity. Conclusions Even after 20 yr of exposure to different intensities of trampling, calcareous grassland vegetation showed only few and spatially limited compositional responses, while its nature conservation value was not affected. Therefore, marked hiking trails are a good compromise between meeting the needs for recreation and environmental education, and the conservation of threatened habitat specialists and should be preferred to alternatives such as undirected access that would result in spatially extensive changes in community structure.